TEACHERS’ STRATEGIES IN ENHANCING STUDENTS’ WRITING SKILLS IN ELEMENTARY SCHOOL - Laura Melati (CV. Fahr Publishing, 2024)
This study aims to explore and synthesize teacher strategies that effectively enhance elementary students’ writing skills, focusing on both instructional practices and motivational factors. Employing a literature review method, the research systematically analyzed recent peer-reviewed articles published between 2020 and 2025 from databases such as ERIC, Scopus, and Google Scholar. The findings reveal that strategies such as scaffolding, teacher feedback, peer review, and genre-based instruction are among the most frequently implemented and effective approaches in elementary writing instruction. These strategies contribute to improving students’ cognitive processes in writing while fostering greater motivation and engagement in the classroom. The novelty of this study lies in its focus on teacher-led implementation, the integration of motivational perspectives, and the underexplored dimensions of sustainability and teacher beliefs in strategy adaptation. It also emphasizes the practical reality of writing instruction in diverse, multilingual classrooms, where teachers serve as both instructors and decision-makers. The review highlights a critical gap in current research—namely, the lack of longitudinal studies that track how writing strategies evolve over time and how teacher reflections influence their sustained application. In conclusion, this study contributes to global discourse by offering a more holistic and practical framework for enhancing elementary writing instruction, while also providing implications for teacher professional development and curriculum reform. Its relevance extends beyond national contexts, supporting international educational goals of improving foundational literacy skills in the early years of schooling.